Analysis Of Financial Performance On The Realization Of Regional Revenue And Expenditure Budget Reports In The Provincial Government Of North Sumatra For The Year 2019-2022 - Putri Salsabila Siregar; Junawan Junawan; Dito Aditia Darma Nasution (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study examines the financial performance of the Government of North Sumatra from 2019 to 2022, focusing on the Revenue and Expenditure Realization Reports (LRA). The analysis uses financial ratios, including the effectiveness of Local Revenue (PAD), financial efficiency, and financial independence, to evaluate budget performance. Findings reveal that the government faced fluctuations in revenue and expenditure realizations, with notable trends in PAD effectiveness, which exceeded planned targets in 2021 and 2022. These outcomes underscore improvements in the local government's ability to manage and optimize revenue, even amidst challenges such as the COVID-19 pandemic. The study emphasizes the importance of efficient financial management for sustaining development and ensuring fiscal autonomy.